Consequences of electronic excitations in CoFe1.90Dy0.10O4 - Kumar, Hemaunt; Singh, Jitendra Pal; Srivastava, R. C.; Negi, P.; Agrawal, H. M.; Asokan, Kandasami; Won, Sung Ok; Chae, Keun Hwa (ELSEVIER SCIENCE BV, 2015)
Present work reports the irradiation induced effects in Dy3+ doped cobalt ferrite nanoparticles in the regime of dominant electronic excitation processes induced by 100 MeV O7+ ion irradiation. Irradiation leads to the deterioration of crystalline phase as envisaged by X-ray diffraction. Crystallite size decreases with the increase of irradiation fluence. Disappearance of certain bands in Raman spectra at higher fluence of irradiation confirms the crystalline disorder induced by electronic excitations. Fourier transform infrared spectra show onset of cation migration from tetrahedral site to octahedral site and vice versa. X-ray absorption fine structure measurements depict the preservation of valence state of metal ions after irradiation. These measurements further infer bond breaking process in irradiated materials. Magnetic measurements carried out on these materials indicate slight increase of saturation magnetization at room temperature followed by the decrease of coercive field. Obtained results are discussed on the basis of appropriate mechanism. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: COBALT FERRITE NANOPARTICLES; ZINC FERRITE; MAGNETIC-PROPERTIES; DIELECTRIC-PROPERTIES; RAMAN-SPECTROSCOPY; ION IRRADIATION; SIZE; TRACKS